Making New Zealand: Celebration and Anti-Myth - Dudding, Michael (Architectural History Aotearoa, 2024)
The Making New Zealand publications were a New Zealand government‐produced series of magazines to celebrate the centenary of the 1840 signing of the Treaty of Waitangi. Each issue of the series (covering topics from infrastructure and defence, to fashion and sport) was to present an objective overview of the history of its subject – within the confines of a publication commemorating New Zealand's history. Joe Heenan, Undersecretary of Internal Affairs, was keen for the centenary celebrations and ephemera to "celebrate 100 years of colonisation," bringing "the bright side of our national progress" before the eyes of the world. While some authors were happy to articulate their topics in support of Heenan's vision, others became interested in producing what they believed to be a more realistic narrative grounded in the social realities of this country, including its negative aspects. Rather than making a case for the maintenance of cultural continuity, these writers sought a national identity arising from cultural adaptation to the specific conditions of New Zealand as a new world. This paper looks at a range of Making New Zealand issues to explore the narratives put forward as retrospective accounts of and normative directives for the design of New Zealand's interior and landscape environments.